Securitization of Bank Assets as a Source of Financing the Innovation Activity - Nikolova, Liudmila Vasilevna; Rodionov, Dmitriy Grigorievich; Mottaeva, Angela Bahauovna (International Journal of Economics and Financial Issues, 2016)
The paper justifies the features of securitization of bank assets as a process and as a source of financing of innovation activity. The place of securitization among financial innovation instruments is defined for this purpose, the basic distinctive features of the securitization model from other financing models are set out, peculiarities of application of three models of securitization (classical, synthetic, corporate) in solving problems of optimization of bank assets and reduction in the risks of banks and in financing of innovation are established. The efficiency of using the model of securitization of bank assets is defined. It is justified that not only the bank that manages credit risk receives the new possibilities in securitization operations, but also so does the client who is interested in reducing the cost of the loan funds used, as well as the investor who receives a highly profitable and at the same time low-risk financial instrument in the implementation of innovative projects at their disposal. Key words: securitization models, bank assets, bank risks, innovation activity, innovative project. JEL Classifications: G11, G21.